2017
DOI: 10.1002/anie.201706757
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Control of the Enantioselectivity of a Supramolecular Catalyst Allows Selecting the Configuration of Consecutively Formed Stereogenic Centers

Abstract: The enantiomeric state of a supramolecular copper catalyst can be switched in situ in ca. five seconds. The dynamic property of the catalyst is provided by the non-covalent nature of the helical assemblies supporting the copper centers. These assemblies are formed by mixing an achiral benzene-1,3,5-tricarboxamide (BTA) phosphine ligand (for copper coordination) and both enantiomers of a chiral phosphine-free BTA co-monomer (for chirality amplification). The enantioselectivity of the hydrosilylation reaction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
69
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 49 publications
2
69
1
Order By: Relevance
“…

The design of an ew class of fluxional biphenyl bisphosphinite (BIBIPHOS) ligands decorated with amino acid-based diamide interaction sites is reported that undergo spontaneous desymmetrization. [2] Much less prevalent are examples where the nature of the chiral element is determined by the interaction itself.Inspired by nature,n ucleobase-derived ligands [3] as well as ligands bearing amino acid-derived interaction sites [4] have been reported, that mimic naturally occurring hydrogen bonding patterns in DNAorinproteins to enantioselectively generate self-assembled ligands with chiral axes.Other examples were reported where chiral molecules were capable of controlling the stereodynamic element of acatalyst [5] such as its helicity [6] or achiral axis [7] through non-covalent bonding.Amore elaborate feature that results from intermolecular interactions between different components of ac atalytic system, that is,d ifferent catalyst molecules,l igands,o r reagents,i st hat formation of aggregates can cause the emergence of nonlinear effects such as the amplification of asymmetric processes. This stereoconvergent behavior of the fluxional BIBIPHOS ligand is triggered by pronounced intermolecular interlocking of the recognition sites,l eading to the formation of as upramolecular assembly,w here the axial orientation of the biphenyl ligand backbone is governed by the chirality of the amino acid moieties.S tereoinduction during catalysis is decoupled from this process and occurs as an immediate consequence of the emergent behavior of the ligands.T his supramolecular system is very robust and has the potential to be adopted for other ligand designs in enantioselective catalysis.

Enantioselective interactions between molecules play apivotal role in aw ide range of natural processes.W hile this interaction is of non-covalent nature,i ti st he basis for molecular recognition and chirality transfer,p rocesses believed to be deeply rooted in natural chiral replication.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…

The design of an ew class of fluxional biphenyl bisphosphinite (BIBIPHOS) ligands decorated with amino acid-based diamide interaction sites is reported that undergo spontaneous desymmetrization. [2] Much less prevalent are examples where the nature of the chiral element is determined by the interaction itself.Inspired by nature,n ucleobase-derived ligands [3] as well as ligands bearing amino acid-derived interaction sites [4] have been reported, that mimic naturally occurring hydrogen bonding patterns in DNAorinproteins to enantioselectively generate self-assembled ligands with chiral axes.Other examples were reported where chiral molecules were capable of controlling the stereodynamic element of acatalyst [5] such as its helicity [6] or achiral axis [7] through non-covalent bonding.Amore elaborate feature that results from intermolecular interactions between different components of ac atalytic system, that is,d ifferent catalyst molecules,l igands,o r reagents,i st hat formation of aggregates can cause the emergence of nonlinear effects such as the amplification of asymmetric processes. This stereoconvergent behavior of the fluxional BIBIPHOS ligand is triggered by pronounced intermolecular interlocking of the recognition sites,l eading to the formation of as upramolecular assembly,w here the axial orientation of the biphenyl ligand backbone is governed by the chirality of the amino acid moieties.S tereoinduction during catalysis is decoupled from this process and occurs as an immediate consequence of the emergent behavior of the ligands.T his supramolecular system is very robust and has the potential to be adopted for other ligand designs in enantioselective catalysis.

Enantioselective interactions between molecules play apivotal role in aw ide range of natural processes.W hile this interaction is of non-covalent nature,i ti st he basis for molecular recognition and chirality transfer,p rocesses believed to be deeply rooted in natural chiral replication.

…”
mentioning
confidence: 99%
“…[2] Much less prevalent are examples where the nature of the chiral element is determined by the interaction itself.Inspired by nature,n ucleobase-derived ligands [3] as well as ligands bearing amino acid-derived interaction sites [4] have been reported, that mimic naturally occurring hydrogen bonding patterns in DNAorinproteins to enantioselectively generate self-assembled ligands with chiral axes.Other examples were reported where chiral molecules were capable of controlling the stereodynamic element of acatalyst [5] such as its helicity [6] or achiral axis [7] through non-covalent bonding. [2] Much less prevalent are examples where the nature of the chiral element is determined by the interaction itself.Inspired by nature,n ucleobase-derived ligands [3] as well as ligands bearing amino acid-derived interaction sites [4] have been reported, that mimic naturally occurring hydrogen bonding patterns in DNAorinproteins to enantioselectively generate self-assembled ligands with chiral axes.Other examples were reported where chiral molecules were capable of controlling the stereodynamic element of acatalyst [5] such as its helicity [6] or achiral axis [7] through non-covalent bonding.…”
mentioning
confidence: 99%
“…

Introduction of competing interactions in the design of asupramolecular polymer (SP) creates pathway complexity. This has contributed to the development of innovative catalysts, [6,7] fluorescent systems, [8,9] self-healing materials, [10,11] and gels, [12,13] among other potential applications.O ne fascinating consequence of the dynamic character of supramolecular assemblies is the capability of molecular building blocks to assemble into distinct thermodynamically or kinetically stable nanostructures. Spectroscopic (FTIR and CD), calorimetric (DSC), and scattering (SANS) techniques show that such ester-bis-ureas self-assemble into three competing rod-like SPs.T he previously unreported low-temperature SP is stabilized by hydrogen bonds between the interfering ester groups and the urea moieties.I ta lso features aw eak macroscopic alignment of the rods.T he other structures form isotropic dispersions of rods stabilized by the more classical urea-urea hydrogen bonding pattern.

…”
mentioning
confidence: 99%
“…[5,6] In such adynamic system, the resolution into one of the diastereomers is dependent on transfer of chiral information from as tereoregulating unit. [25,26] Theg roup of Reek demonstrated that stereocontrol in asupramolecular catalyst system could be achieved by either entrapment of the rhodium center in asupramolecular metallocage [27] or by molecular recognition of ac hiral cofactor in ab identate ligand. [12][13][14][15][16] Recently,control of axial chirality in a tropos ligand was demonstrated by association of small chiral molecules through hydrogen bonding.…”
mentioning
confidence: 99%
“…[24] Theg roups of Raynal and Vidal-Ferran achieved stereocontrol through the coassembly of chiral benzene-1,3,5-tricarboxamides (BTA) with achiral BTAs functionalized with P-donor moieties in ahelical scaffold. [25,26] Theg roup of Reek demonstrated that stereocontrol in asupramolecular catalyst system could be achieved by either entrapment of the rhodium center in asupramolecular metallocage [27] or by molecular recognition of ac hiral cofactor in ab identate ligand. [9,28] Also chiral phosphoric acids have been used for supramolecular stereoregulation through ion pairing in asymmetric catalysis.…”
mentioning
confidence: 99%